Aircraft dynamics and automatic control - McRuer, Duane T.; Ashkenas, Irving Louis; Graham, Dunstan (Princeton legacy library., 1973)
Aeronautical engineers concerned with the analysis of aircraft dynamics and the synthesis of aircraft flight control systems will find an indispensable tool in this analytical treatment of the subject. Approaching these two fields with the conviction that an understanding of either one can illuminate the other, the authors have summarized selected, interconnected techniques that facilitate a high level of insight into the essence of complex systems problems. These techniques are suitable for establishing nominal system designs, for forecasting off-nominal problems, and for diagnosing the root causes of problems that almost inevitably occur in the design process. A complete and self-contained work, the text discusses the early history of aircraft dynamics and control, mathematical models of linear system elements, feedback system analysis, vehicle equations of motion, longitudinal and lateral dynamics, and elementary longitudinal and lateral feedback control. --